Some aspects on the issue of investment attractiveness of the agrarian sector of economy of Ukraine. - Панченко, В. В. (Theory and practice of jurisprudence, 2016)
Problem setting. The financial and economic crisis has caused a significant reduction of internal sources of investment, and international financial resources are virtually inaccessible due to bad investment attractiveness of Ukraine. Recent research and publications analysis. In fact, even advanced economies define innovation and investment a priority to enhance the competitiveness of the economy and support a sufficient level of investment attractiveness of the country. Paper objective. Purpose of this report - the study of a number of questions about the investment attractiveness of the agrarian sector of economy of Ukraine. Paper main body. One of the strategic priorities for innovation and investment activity in the years 2011-2021 is a technological upgrade and development just agriculture. Implementation of innovative investment model of agricultural development and proper implementation of public administration by providing state support for innovation and investment development of the agricultural sector will increase its attractiveness. Conclusions of the research. Low innovation and investment activity entities competitiveness in agriculture and the agricultural sector of Ukraine is the result of the unstable political situation, the imperfections of the state of innovation and investment policy, gaps in the innovation and investment legislation, lack of proper institutional support for innovation and investment market and its mechanisms implementation, lack of effective mechanisms for public-private partnerships.